Association of Mannan Binding Lectin to Liver Fibrosis in Chronic HCV Patients - Wafaa Ezzat (Journal of Global Pharma Technology, 2019)
The interaction between viral and host immune factors plays an important role in natural history of chronic HCV infection .We aimed to determine serum level of MBL and its relation to grades of liver fibrosis in chronic HCV patients.we studied the impact of serum level of MBL on early virological responsein chronic HCV patients.subjects and methods: included 70 HCV patients (40 HCV patients with liver fibrosis grades <F3 (group Ι) &30 HCV patients with liver. fibrosis ≥F3 (groupΙΙ) according to METAVIR score), who fulfilled inclusion & exclusion criteria of the National Egyptian treatment protocol of treatment of CHC, in addition to 16 control subjects. All studied cases were subjected to history taking, thorough clinical examination, routine investigation(fasting blood sugar, serum creatinine, alkaline phosphatase, ALT, AST, total bilirubin, albumin ,complete blood picture ,prothrombin activity, alpha feto-protein, TSH) ,  abdominal ultrasonography and liver biopsy in addition to ELISA for MBL. Results: mean values of MBL was significantly increased among group 2 patients more than that of group 1(P=0.001). After 12wk of combined therapy, it was found that 61 patients (87.14%) were responders to antiviral therapy, while9 patients (12.85%) were non responders.  The mean value of MBL among responders was 64.44± 26.75 while it was 90.41± 82.41 without any statistically significant differences. So it can be concluded that MBL plays an important role in the pathogenesis of liver fibrosis in HCV liver disease. MBL has no impact on early virological response among patients with chronic HCV infection.